(untitled) (Journal of Philosophy Culture and Political Science, 2015)
East patristika is the complete ontologic picture of life including anthropological, cosmological, gnoseological, theological ideas. It reflects on process of philosophical works of religious thinkers and represents a cultural, philosophical, religious phenomenon of orthodox outlook. The Byzantine culture was considerably enriched with elements of culture of the people of the East that gave it unique color. The contribution of the Eastern people to formation and development of the Byzantine civilization is essential. For Christian dogma there was nothing more dangerous and more necessary, than systematization of philosophical knowledge for the purpose of the solution of theological tasks. Orientation of Christian culture to antique heritage was most of all shown in relation to the most concentrated expression of the essence of an ellinstvo – philosophy. Fight was aggravated by the fact, that against Christianity in III-Y of centuries there were not systems of everyday morals, like stoicism and an epikureizm, but the original philosophizing about life undertaking to answer deep questions of human spirit.